2002
DOI: 10.1375/twin.5.3.156
|View full text |Cite
|
Sign up to set email alerts
|

How Mothers Cope with the Death of a Twin or Higher Multiple

Abstract: Estimates suggest up to 15% of multiples grow up as singleton survivors. Few studies have reported how bereaved multiple birth mothers with a surviving multiple cope with their bereavement. Using the population-based Western Australian Twin Child Health study database and other sources, we interviewed 66 bereaved mothers with at least one surviving multiple. For many, this contact was the first acknowledgement of their status as multiple birth mothers since their loss. The Beck Depression Inventory 2nd Edition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…In this data set, a total of 27 research reports used the PGS to measure perinatal grief during bereavement following a pregnancy loss. The PGS has been frequently used in concert with other tools to produce correlations of grief after perinatal loss with variables such as depression (Zeanah et al 1993, Swanson et al 2002, Burgoine et al 2005, marital satisfaction (Lin & Lasker 1996), impact of other life events (Johnson & Puddifoot 1996, Hunfeld et al 1997a, Kroth et al 2004, Serrano & Lima 2006 and social support (Lin & Lasker 1996, Kroth et al 2004). These findings suggest that perinatal bereavement is a complex phenomenon and while its chief manifestation is grief, it is influenced by multiple variables that may not be captured in a single measurement tool nor conceptualized as only the experience of grief.…”
Section: Pragmatic Principlementioning
confidence: 99%
See 2 more Smart Citations
“…In this data set, a total of 27 research reports used the PGS to measure perinatal grief during bereavement following a pregnancy loss. The PGS has been frequently used in concert with other tools to produce correlations of grief after perinatal loss with variables such as depression (Zeanah et al 1993, Swanson et al 2002, Burgoine et al 2005, marital satisfaction (Lin & Lasker 1996), impact of other life events (Johnson & Puddifoot 1996, Hunfeld et al 1997a, Kroth et al 2004, Serrano & Lima 2006 and social support (Lin & Lasker 1996, Kroth et al 2004). These findings suggest that perinatal bereavement is a complex phenomenon and while its chief manifestation is grief, it is influenced by multiple variables that may not be captured in a single measurement tool nor conceptualized as only the experience of grief.…”
Section: Pragmatic Principlementioning
confidence: 99%
“…Zeanah et al (1993) studied the grief responses in women who electively terminated pregnancies for foetal anomalies and concluded that their grief was as intense as those with spontaneous losses. The experience of perinatal bereavement has been studied at various intervals, such as 1 year after miscarriage (Swanson et al 2007), 4 months after miscarriage (Adolfsson et al 2006) and even years after the death of an infant (Hunfeld et al 1997b, Schaap et al 1997, Swanson et al 2002.…”
Section: Linguistic Principlementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is commonly unrecognised both by health professionals and friends who may offer minimising reassurance such as ‘well you’ve still got one baby’, which prohibits the expression of grief for the baby who will not be born. The coincidence of bereavement and pregnancy presents a psychological paradox and may lead to delayed or disturbed grief reactions and disrupt the growth of secure mother–infant attachment 7,8 …”
mentioning
confidence: 99%
“…Much of what has been said by Swanson et al (2002) and Kollantai (2002) of the problems and needs of bereaved parents of twins also, of course, applies to parents of higher multiple birth children. However there are some additional considerations, especially in relation to multifetal pregnancy reduction.…”
mentioning
confidence: 99%